A critical analysis and comparative study on the tax burden of South African individual taxpayers from the 2003 to 2019 tax years - Ndlovu, Kethabile (My University, 2020)
Personal income tax (PIT) is the largest source of tax revenue collected by the South African Revenue Service (SARS) and it has accounted for an average of 35% of the total tax revenue between the 2003 and 2019 years of assessment (SARS, 2010& 2019). South Africa uses a progressive tax system to determine the taxable liability of individuals. In the 2017 tax year the top marginal tax rate for individuals was increased from 41% to 45%, making SARS one of the highest taxing authorities in the world(Trading Economics, 2019b). The contribution of PIT to total tax revenue seems to be growing steadily in the period under review, as compared to the contributions made from corporate income tax (CIT) and value-added tax (VAT) (SARS, 2019a). In a country characterised by high unemployment rate, social inequalities, political instability, job cuts, recurring recessionary phases, labour unrest, declining foreign investments and widening national debt, the habit of using tax revenue to fund government spending and to support the fiscal policy becomes inevitable and the only readily available option. Since PIT is the main contributor to tax revenue, this raises the question: “is the tax borne by individuals reasonable and is the dependence on PIT as the main source of revenue a sustainable and effective way to improve the social and economic challenges faced by South Africa?” The purpose of this study is, firstly, to determine whether South African individuals carry a heavy tax burden as compared to taxpayers in other countries with similar economic and social models, using different quantitative methods. This paper will analyse the tax years from 2003 to 2019. This study will underline the effects that dramatic changes in the economy or tax system, such as the global financial crisis in 2008 and the adoption of the Tax Administration Act (TAA) in 2011, had on PIT levels. Secondly, the study will seek to highlight the economic and social impacts of taxing individuals too heavily. Lastly, the study will recommend the best possible tax policies and reforms that are successful in other countries that could possibly be implemented in South Africa to curb the tax burden borne by individuals
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce specializing in Taxation, 2020